2006
DOI: 10.1136/hrt.2005.073791
|View full text |Cite
|
Sign up to set email alerts
|

Major impact of admission glycaemia on 30 day and one year mortality in non-diabetic patients admitted for myocardial infarction: results from the nationwide French USIC 2000 study

Abstract: Objective: To analyse the short and long term prognostic significance of admission glycaemia in a large registry of non-diabetic patients with acute myocardial infarction. Methods: Assessment of short and long term prognostic significance of admission blood glucose in a consecutive population of 1604 non-diabetic patients admitted to intensive care units in France in November 2000 for a recent (( 48 hours) myocardial infarction. Results: In-hospital mortality, compared with that of patients with admission glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
57
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 26 publications
4
57
1
2
Order By: Relevance
“…Also, despite the lower blood This is the first study to assess the association of glycemic state upon hospital admission with the myocardium area at risk and myocardial salvage in a large cohort of patients with STEMI. Our data suggest that the excessive myocardial damage (5-8) and adverse prognosis (3,5,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) reported in patients with hyperglycemia are the results of a larger myocardial area at risk, and not of a smaller myocardial salvage. Similarly, since there was no association between hyperglycemia and infarct size when adjusting for the area at risk, the current study demonstrates that the association between hyperglycemia and infarct size is dependent on the size of the area at risk, and hyperglycemic patients can therefore be considered to be at higher risk per se.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Also, despite the lower blood This is the first study to assess the association of glycemic state upon hospital admission with the myocardium area at risk and myocardial salvage in a large cohort of patients with STEMI. Our data suggest that the excessive myocardial damage (5-8) and adverse prognosis (3,5,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) reported in patients with hyperglycemia are the results of a larger myocardial area at risk, and not of a smaller myocardial salvage. Similarly, since there was no association between hyperglycemia and infarct size when adjusting for the area at risk, the current study demonstrates that the association between hyperglycemia and infarct size is dependent on the size of the area at risk, and hyperglycemic patients can therefore be considered to be at higher risk per se.…”
Section: Discussionmentioning
confidence: 83%
“…The mechanisms behind reperfusion injury have not been fully elucidated, but hyperglycemia, which is observed in approximately half of patients with STEMI upon hospital admission (3), may be unfavorable during reperfusion and has been linked to the subsequent injury (4). Previous studies have demonstrated larger infarct size (5)(6)(7)(8) and poorer prognosis in patients with hyperglycemia upon hospital admission compared with patients without hyperglycemia, both in patients with and without diabetes mellitus (3,5,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Until now, the impact of hyperglycemia on myocardial salvage has been evaluated in only a limited number of patients (21), and no data exist regarding the relationship between hyperglycemia and area at risk.…”
mentioning
confidence: 99%
“…R ecent studies have emphasized the prognostic value of high blood glucose levels in patients with acute myocardial infarction (AMI) (1)(2)(3)(4)(5)(6). Previous investigations focused on the relationship between random blood glucose on admission and outcome.…”
Section: Diabetes Care 30:960 -966 2007mentioning
confidence: 99%
“…12,13,14,15 Alternatively, elevated blood glucose levels per se adversely affect outcome through the cumulative effects of several mechanisms, including induction of endothelial dysfunction, 16 oxidative stress, 7,8 hypercoagulability, and impaired fibrinolysis . 9 Lastly, admission hyperglycemia may not be only the cause of more severe myocardial damage, but also its consequence. Large infarcts are more likely to cause catecholamine release, which affect fatty acid and glucose homeostasis.…”
Section: Discussionmentioning
confidence: 99%